2018
DOI: 10.1002/jbm.a.36528
|View full text |Cite
|
Sign up to set email alerts
|

Injectable hydrogels based on glycyrrhizin, alginate, and calcium for three‐dimensional cell culture in liver tissue engineering

Abstract: Injectable hydrogels have been paid more attentions on cell therapy and tissue regeneration resulting from the applications in minimally invasive surgical procedures with ease of handling and complete filling of defect area. Here, a biodegradable and injectable in situ hydrogel formed by glycyrrhizin (GL), alginate (Alg), and calcium (Ca) was developed for three‐dimensional (3D) cell culture. Differential scanning calorimetry (DSC), X‐ray diffraction (XRD), scanning electron microscope (SEM) and rheology analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…In a recent study, both glycyrrhizin (GL) and DOX were encapsulated into alginate (ALG) nanogel particles via the phase inversion temperature emulsification method; the obtained drug-loaded alginate nanogels (DOX/GL-ALG NGPs) exhibited not only the hepatocellular carcinoma targeting property by GL, but also the synergistic antitumor effects of GL and DOX ( Figure 9) [107]. In addition, ALG nanogels also presented favorable biocompatibility and low toxicity to hepatic tissues by controlled drug release [108]. These studies also implied that nanogels are an ideal nanoplatform for combination therapy.…”
Section: Combinational Chemotherapymentioning
confidence: 99%
“…In a recent study, both glycyrrhizin (GL) and DOX were encapsulated into alginate (ALG) nanogel particles via the phase inversion temperature emulsification method; the obtained drug-loaded alginate nanogels (DOX/GL-ALG NGPs) exhibited not only the hepatocellular carcinoma targeting property by GL, but also the synergistic antitumor effects of GL and DOX ( Figure 9) [107]. In addition, ALG nanogels also presented favorable biocompatibility and low toxicity to hepatic tissues by controlled drug release [108]. These studies also implied that nanogels are an ideal nanoplatform for combination therapy.…”
Section: Combinational Chemotherapymentioning
confidence: 99%
“…Hence, scaffolds fabricated by 3D printing hold new promise in creating functional liver tissues [127]. Recently, an injectable hydrogel made from glycyrrhizin (GL), alginate (Alg), and calcium (Ca) was designed for application in LTE, and the GL–Alg–Ca hydrogel could maintain proliferation and liver specific functions of a hepatic cell line [128].…”
Section: Hydrogels For Ltementioning
confidence: 99%
“…Although GL or GA by polymer-drug conjugate to construct the targeting delivery system showed active liver targeting effect, the immunoregulatory and anti-inflammatory effects of GL or GA were decreased dramatically by steric hindrance effect. Moreover, our recent study showed that the injectable GL-ALG hydrogels existed good biological activity for three-dimensional cell culture in liver tissue engineering 18.…”
Section: Introductionmentioning
confidence: 99%